2013
DOI: 10.1002/ece3.533
|View full text |Cite
|
Sign up to set email alerts
|

Facing the crowd: intruder pressure, within‐group competition, and the resolution of conflicts over group‐membership

Abstract: Recent theory in social evolution has been mainly concerned with competition and cooperation within social groups of animals and their impact on the stability of those groups. Much less attention has been paid to conflicts arising as a result of solitary floaters (outsiders) attempting to join groups of established residents (insiders). We model such conflicts over group-membership using a demographically explicit approach in which the rates of births and deaths in a population determine the availability of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
(97 reference statements)
0
16
0
Order By: Relevance
“…Population density has been predicted to be a critical factor in determining the ability of resident males to resist immigrants [Port & Johnstone, 2013], and studies of multiple Verreaux's sifaka populations in different habitats can highlight how such factors can influence dispersal patterns.…”
Section: Am J Primatolmentioning
confidence: 99%
See 1 more Smart Citation
“…Population density has been predicted to be a critical factor in determining the ability of resident males to resist immigrants [Port & Johnstone, 2013], and studies of multiple Verreaux's sifaka populations in different habitats can highlight how such factors can influence dispersal patterns.…”
Section: Am J Primatolmentioning
confidence: 99%
“…For instance, predation risk, population density, and home range size and overlap may determine whether becoming a solitary male (floater) is a viable strategy because extragroup males may not only be vulnerable to predation [Struhsaker, 1969;Steenbeek et al, 2000] but also cannot afford the travel costs needed to monitor highly spread out potential destination groups [Moore, 1999]. High intruder pressure due to high population density [Moore, 1999;Borries et al, 2011;Shonfield et al, 2012], floater density [Port & Johnstone, 2013], many extra-group males relative to the number of female groups [Cords, 2002], and/or mean number of males per group [Moore, 1999;Borries et al, 2011] can reduce the ability of resident males to resist immigration attempts [Moore, 1999;Port & Johnstone, 2013] and thus lower immigration costs for dispersing males. Males with high competitive ability are more likely to acquire the dominant position in a group by ousting resident males with aggressive takeovers [van Noordwijk & van Schaik, 2004], whereas less competitive males may enter new groups unobtrusively as subordinates [van Noordwijk & van Schaik, 2001], reside in all-male bands [e.g., Hanuman langurs: Sommer & Rajpurohit, 1989], or become floaters.…”
Section: Introductionmentioning
confidence: 99%
“…Joint mate and/or territorial defense may be especially important if floaters (i.e. solitary individuals without territories of their own) are prevalent in the area [Port and Johnstone, 2013;Thompson, 2015]. Indeed, a study of Azara's owl monkeys (Aotus azarai) revealed that encounters with floaters can lead to high turnover rates among pair-mates [Fernandez-Duque and Huck, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the rate at which alpha male replacements occur is variable, both within and between species. As noted above, the likelihood of challenges to the alpha position has been linked to the density of non group males (Butynski, , ; Hrdy, ; Port & Johnstone, ), which may be greater in species with uni‐male, multi‐female social units (Janson & van Schaik, ). Larger female group sizes also may increase the rates at which alpha male replacements occur because these groups are more attractive to non group males (e.g., Beehner & Bergman, ; A. seniculus , Crockett & Janson, ; T. gelada , Dunbar, ; C. capucinus , Fedigan & Jack, ).…”
Section: Introductionmentioning
confidence: 99%